Comparative study of efficacy of tramadol versus nalbuphine as an adjuvant to intrathecal bupivacaine - Sathyasuba Meenakshi Sundaram; Srinidhi Narayanan; Gayathri Ramesh; Raghuraman M Sethuraman; Bhagawathi B (Journal of Krishna Institute of Medical Sciences University)
Background: Spinal anesthesia is commonly used for infra umbilical surgeries due to its effective analgesia and favorable safety profile. However, local anesthetics like bupivacaine alone provide limited postoperative pain relief. Aim and Objectives: This randomized double-blind study aimed to compare the duration of analgesia of intrathecal tramadol and nalbuphine added to hyperbaric bupivacaine for infra umbilical surgeries, as there are limited studies on this comparison. Material and Methods: A total of 60 patients scheduled for elective infraumbilical surgeries at a tertiary care center were randomized into two groups. Group T received 25 mg of tramadol, and Group N received 1 mg of nalbuphine, both as adjuvants to 0.5% hyperbaric bupivacaine. The primary outcome was the duration of analgesia. Secondary outcomes included the onset and duration of sensory and motor blocks, hemodynamic stability, time to rescue analgesia and incidence of side effects. Results: Although nalbuphine provided a slightly faster onset of sensory and motor block (4.0 ± 1.0 and 5.7 ± 1.2 minutes respectively) than tramadol (4.3 ± 1.1 and 6.0 ± 1.3 minutes respectively), it was statistically insignificant (p = 0.238, 0.314). Also, the duration of analgesia was significantly longer in the nalbuphine group (8.2 ± 1.3 hours) compared to the tramadol group (7.5 ± 1.2 hours) (p = 0.045). Both groups maintained stable hemodynamic profiles, and there was no significant difference in the incidence of side effects. Conclusion: Nalbuphine, when added to intrathecal bupivacaine, provides a longer duration of analgesia with comparable onset times and safety profile. Thus nalbuphine can be considered a more effective adjuvant for enhanced postoperative pain relief.